ANALYSIS OF THE VISIT BEAUTIFUL WEST SUMATRA 2023 LOGO WORK THROUGH VISUAL SEMIOTICS APPROACH - Aryoni Ananta; Haris Satria (Yayasan Sinergi Widya Nusantara, 2023)
Purpose: Visit Beautiful West Sumatra (VBWS) is an activation program for post-pandemic tourist visits which has become the starting point for the revival of tourism in West Sumatra. One of the important points in this activation program is the identity design in the form of a logo. This study aimed to analyze the Visit Beautiful West Sumatra 2023 logo work through a visual semiotics approach. Research methods: This study is qualitative using descriptive methods. Findings: The results showed that the logo has layers of expression/senses (signifier) ??and layers of meaning/perception (signified) with the spirit of synergy, collaboration, and innovation. Implications: The logo, as part of the identity, has been implemented for West Sumatra tourism stakeholders.